Sprinting to the Finish Line: The Benefits and Challenges of Book Sprints in OER Faculty-Graduate Student Collaborations - Zapata, Gabriela C. (International Review of Research in Open and Distributed Learning, 2020)
This article investigates the results of a book sprint experience whose main objective was the development of instructional modules for an open textbook for the teaching of Spanish as a second language. Six graduate students at a public American university participated in the project for a week, working in pairs in the creation of activities that required the incorporation of the tenets of the dual pedagogical frameworks of performance- and literacy-based instruction (as realized through learning by design). Data were collected through both an opinion survey and the assessment of samples of the participants’ products. The results of the survey showed that graduate students felt that being part of the book sprint had been beneficial both at the professional and personal levels, but they had also experienced difficulties similar to those reported in previous studies. The products analyzed pointed to a lack of connection between the required pedagogical tenets and the materials developed, which has also been reported in existing works on pre- and in-service teachers as materials developers. The article discusses how these results could have been a consequence of the structure of the book sprint, and it offers recommendations for future activities of this kind.